Acquired and Congenital Ocular Toxoplasmosis Experimentally Induced in Calomys callosus (Rodentia, Cricetidae) - Maria de Fátima Pereira; Deise Aparecida Oliveira Silva; Eloisa Amália Vieira Ferro; José Roberto Mineo (Memorias do Instituto Oswaldo Cruz, 1999)
An experimental model for acquired and congenital ocular toxoplasmosis as well as a model to induce experimental autoimmune uveitis (EAU) was investigated in Calomys callosus. Toxoplasma gondii, ME-49 strain, was used to infect males and pregnant- and not pregnant-females while S-antigen, a major glycoprotein of the retinal photoreceptor cell, was used to induce EAU. The ocular lesions elicited by T. gondii were characterized by the presence of cysts, free tachyzoites and inflammatory cells in the retina or related tissues. In the congenital form, 40% of the fetus presented ocular lesions, i.e., presence of cysts in the retina, vitreous, and extra-retinal tissues. In the acquired form, 75% of the females and 50% of the males presented unilateral ocular cysts both at 21 and 47 days post-infection. It was also demonstrated that S-antigen was not uveitogenic in the C. callosus model. No lesion was observed in the animals exclusively immunized with this retinal component, even when jacalin was used as additional adjuvant for polyclonal response to the retinal antigen. It can be concluded that C. callosus may constitute in a promising model for study both acquired and congenital ocular toxoplasmosis, particularly when it is important to make sure that a non autoimmune process is involved in the genesis of the ocular infection.